Criminal Liability for Owners of Protected Animals Without a Permit - Maria, Juliya; Indrayani, Leni (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The abundance of animal natural resources is a gift from God Almighty intended for countless Indonesian people. With these diverse types of biological natural resources being very rarely found in their habitats, rare animals whose populations are difficult to find are almost extinct, due to destruction of forests which causes the loss of the protective function of animal life support systems and their ecosystems from the wild, the impact is the extinction of protected animals, illegal wildlife trade and ownership of animals without permits, and the government has issued a law that regulates the prohibition of ownership of wild animals for keeping and determines which animals can and which cannot be kept by the community. Based on the research results, the legal regulations governing the ownership of animals that may be owned for keeping are only types of animals that are not protected, while those that are protected by law are prohibited from being owned and kept and this act is included in the criminal act of owning protected animals without permission, and the perpetrators can be subject to criminal sanctions and can be punished with administrative fines.